Technical and economic efficiency of methods for extracting genomic DNA from Meloidogyne javanica - Carvalho, Vanessa Rafaela de [UNESP]; Wilcken, Sílvia Renata Siciliano [UNESP]; Wilcken, Carlos Frederico [UNESP]; Castro, Bárbara Monteiro de Castro e; Soares, Marcus Alvarenga; Zanuncio, José Cola (Elsevier, 2019)
Plant parasitic nematodes reduce the production of agricultural crops. Species diagnosis is essential to predict losses, determine economic damage levels and develop integrated pest management programs. DNA extraction techniques need to be improved for precise and rapid molecular diagnosis of nematodes. The objective of the present study was to evaluate the efficiency of DNA extraction and amplification by PCR, cost and execution time by Chelex, Worm Lysis Buffer Method (WLB), Holterman Lysis Buffer Method (HLB) and FastDNA methods for nematodes of the Meloidogyne genus. The qualitative and quantitative efficiency of DNA extraction varied between methods. The band size of the amplified PCR product with WLB, Chelex and HLB methods was 590 bp. Extraction with the FastDNA is not recommended for DNA extraction from nematodes because it results in a low DNA concentration without bands in PCR amplification, besides presenting high cost. The efficiency of the WLB method to extracting DNA from Meloidogyne javanica was greater, ensuring a higher concentration and purity of the extracted material and guaranteeing lower costs and greater ease of PCR amplification.
Keywords: 28S rDNA; DNA extraction; Meloidogyne spp.; Nematode identification; PCR